Pendampingan Siswa dengan Metode Membaca, Menulis, dan Berhitung di Desa Terak, Kecamatan Simpang Katis - Hevitria, Hevitria; Tohir, Muhamad (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
The implementation of the "calistung" (reading, writing, and arithmetic) tutoring aims to enhance students' literacy and numeracy skills. This activity is part of a community service program carried out by two lecturers and students. The purpose of this service is to provide guidance to students in recognizing and mastering the skills of reading, writing, and arithmetic (calistung). The methods used in this service include community situation analysis (initial observation) and work procedures to realize the proposed methods. The activity was held in October 2024, involving 35 tutoring participants. The results of this service show that the tutoring participants gained an improved understanding of the calistung method, ranging from grades 1 to 6. This is reflected in the tutoring material provided, which facilitates their learning in reading, writing, and arithmetic. Additionally, a positive impact is seen in the involvement of parents, who are pleased with the tutoring support provided to their children, strengthening the connection between the tutoring participants and their parents.